1982
DOI: 10.1126/science.7043737
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Disease—a Tick-Borne Spirochetosis?

Abstract: A treponema-like spirochete was detected in and isolated from adult Ixodes dammini , the incriminated tick vector of Lyme disease. Causally related to the spirochetes may be long-lasting cutaneous lesions that appeared on New Zealand White rabbits 10 to 12 weeks after infected ticks fed on them. Samples of serum from patients with Lyme disease were shown by indirect immunofluorescence to contain antibodies to this agent. It is suggested that the newly discovered spirochete is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
1,332
1
42

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,594 publications
(1,387 citation statements)
references
References 13 publications
12
1,332
1
42
Order By: Relevance
“…The spirochete Borrelia burgdorferi is the causative agent of Lyme disease (Burgdorfer et al, 1982). Lyme disease is a multi-systemic disorder which, if not treated early, can develop into chronic infection (Steere, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The spirochete Borrelia burgdorferi is the causative agent of Lyme disease (Burgdorfer et al, 1982). Lyme disease is a multi-systemic disorder which, if not treated early, can develop into chronic infection (Steere, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous lipoprotein most studied in the brain is the bacterial outer surface protein A (ospA), which is produced by B. burgdorferi [12,13]. B. burgdorferi causes Lyme disease, which is the most common tick-borne infection in Europe and in North America [14].…”
Section: Introductionmentioning
confidence: 99%
“…
The spirochete Borrelia burgdorferi is a tick-borne obligate parasite whose normal reservoir is a variety of small mammals [1]. Whereas infection of these natural hosts does not lead to disease, infection of humans can result in Lyme disease, as a consequence of the human immunopathological response to B. burgdorferi [2,3].
…”
mentioning
confidence: 99%
“…suggested that the epidemiology of Lyme disease indicated transmission by an arthropod vector due to the geographic clustering of patients in rural areas and the seasonal occurrence of the symptoms [7]. Subsequently, Dr. Willy Burgdorfer and coworkers observed spirochetes in the midgut tissues from ticks collected in a Lyme disease endemic area [1]. These spirochetes produced a skin rash resembling erythema migrans when injected into rabbits, and sera from Lyme disease patients reacted with the bacteria in indirect immunofluorescence assays.…”
mentioning
confidence: 99%